2021
DOI: 10.2106/jbjs.rvw.20.00154
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Following Ulnar Collateral Ligament Reconstruction in Overhead-Throwing Athletes

Abstract: » The prevalence of ulnar collateral ligament (UCL) injury and UCL reconstruction (UCL-R) continues to rise, causing morbidity in overhead-throwing athletes.» Postoperative rehabilitation protocols are essential for proper healing of the reconstructed ligament and safely returning athletes to competition, yet there is no uniformly accepted standard of care.» UCL-R rehabilitation has traditionally been guided by expert opinion and conventional wisdom rather than scientific studies, resulting in substantial vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Despite no standard consensus on an evidence-based protocol, many studies have reviewed the available literature to identify the core principles of recovery. [74][75][76][77] Current principles of UCL reconstruction (UCL-R) can be divided into 4 phases: (1) immediate postoperative, (2) intermediate strengthening, (3) advanced strengthening, and (4) return to activity. 75,77 The first phase (weeks 0 to 3) is directed at protecting the healing graft and gradual restoration of elbow ROM.…”
Section: Ucl Tear Rehabilitation Protocol and Timelinementioning
confidence: 99%
See 4 more Smart Citations
“…Despite no standard consensus on an evidence-based protocol, many studies have reviewed the available literature to identify the core principles of recovery. [74][75][76][77] Current principles of UCL reconstruction (UCL-R) can be divided into 4 phases: (1) immediate postoperative, (2) intermediate strengthening, (3) advanced strengthening, and (4) return to activity. 75,77 The first phase (weeks 0 to 3) is directed at protecting the healing graft and gradual restoration of elbow ROM.…”
Section: Ucl Tear Rehabilitation Protocol and Timelinementioning
confidence: 99%
“…[74][75][76][77] Current principles of UCL reconstruction (UCL-R) can be divided into 4 phases: (1) immediate postoperative, (2) intermediate strengthening, (3) advanced strengthening, and (4) return to activity. 75,77 The first phase (weeks 0 to 3) is directed at protecting the healing graft and gradual restoration of elbow ROM. 75,77 A systematic review by Lightsey et al 74 analyzed 30 rehabilitation protocols after UCL-R and found that most protocols recommend immediate splinting of the elbow at 90 for approximately 2 weeks, followed by a functional brace to be worn until approximately 4 to 6 weeks semioperatively.…”
Section: Ucl Tear Rehabilitation Protocol and Timelinementioning
confidence: 99%
See 3 more Smart Citations